Effects of carbonaceous susceptors on microwave pretreatment of waste activated sludge and subsequent anaerobic digestion. (February 2021) - Bozkurt, Yigit C.; Lafaille, Ritchie; Lu, Dingnan; Zhang, Xiaoqi; Giles, Robert; Apul, Onur G.
Abstract: Pretreatment of waste activated sludge is an accepted approach to improve the anaerobic digestion performance by accelerating hydrolysis. Recently, microwave irradiation has been gaining attention as a pretreatment method because it accomplishes remote, rapid, and targeted heating of sludge and assists the release of soluble organic constituents. This study demonstrates the effect of hyper-reactive dielectric carbon nanofiber additives on amplified microwave pretreatment and subsequent anaerobic digestion and compares to traditional activated carbons for the first time. Our findings show that when carbon nanofibers are used, microwave pretreatment increases the soluble chemical oxygen demand from 73 to 924 mg L −1 . This increase in sCOD corresponds to 25% improvement when compared to microwave pretreatment alone. Moreover, carbon nanofibers facilitate more biogas production (i.e., 24%) with higher methane content (i.e., 46%) when compared to no pretreatment. Our findings also provide engineering insights within a techno-economic framework for carbon nanomaterial-augmented microwave pretreatment. Graphical abstract: Unlabelled Image Highlights: Carbon nanofibers show 10–20 times faster microwave heating than activated carbons. Carbon nanofibers increase soluble COD by 25% compared to MW pretreatment alone. CNF in AD increases biogas quantity by 24% compared to no pretreatment. CNF in AD increases biogas methane content by 46% compared to no pretreatment. Cost of carbon nanomaterials drives the cost of implementing the technology.